(3JGQjN OhdI GdJQc aj Gdjefs - (3GHf GdegOj Hf GdgGOjs
(3ChdgG (B:s
(3MeO Gdef LYd Ggd HjJ ajg eMeO eKGHI ddfGU hCefkG hHYO abO SCdfi ef dG GLjO YeG GeQ Cf CLeY eG YdeJg ef SJQI ehdGfG CejQ GdeDefjf GdefUhQ HGddg GdbGSe Hf eMeO Hf Ydi s
(3BNQgG (B:s
(3hSCJi Gf TGA Gddg eaUdkG PcQ eG LQi HYO ehJ GdGeGe GdeDjO Ydjg GdSdGe ai SjQI GdGeGe GdeJhcd Gf TGA Gddg s
(3HgG fXGe GdJYbjHIs
(3hfWf GfgG ShOg ddeDdas
(3hjHOG SfI (B986 (3g` ai fUa QeVGfs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3eJaQbGJs